Factors Related to Compliance in Taking Medication among Pulmonary Tuberculosis (TB) Patients - Ai Fitriati; Rita Ramayulis; Prihayati (KHD Production, 2024)
In the treatment of pulmonary tuberculosis (TB) requires a long period of time so that consistency of patient compliance in taking medication is needed. Patient compliance in taking medication is very important, this aims to control the number of TB cases. Compliance in taking medication needs to be supported by increasing knowledge, motivation and family support. This study aims to determine the factors related to compliance in taking medication in pulmonary tuberculosis (TB) patients at the Cikedal Health Center, Cikedal District, Pandeglang Regency. This type of research is quantitative with a descriptive analytical research design and uses a cross-sectional approach. The number of samples in this study was 30 with a sampling technique using total sampling, the data collection tool used was a questionnaire with bivariate analysis using the Chi-Square test. The results of the study showed that factors related to compliance in taking medication were education level p value = 0.009, knowledge level p value = 0.001, attitude p value = 0.004, family support p value = 0.004, and access to treatment p value = 0.001. There needs to be increased socialization regarding TB disease so that the community can be more compliant with the treatment being carried out.